SISTEM INFORMASI ABSENSI KARYAWAN PADA CV. MANHA DIGITAL BERBASIS ANDROID - Tabrani Muhamad; Suhardi Suhardi; Hananda Priyandaru (Politeknik Bisnis Indonesia, 2022)
Technology is currently developing very rapidly, especially in the field of information system development, forcing companies or agencies to adapt, and must take advantage of existing opportunities to facilitate the performance of all employees. During the COVID-19 pandemic, all companies were forced to employ all employees from home. CV Manha Digital updated the employee attendance policy which was previously done manually by taking daily attendance at the company. During the pandemic, in support of government policies that require working from home to avoid physical contact between employees and reduce the spread of the corona virus, an Android-based attendance information system is needed that allows employees to take attendance using cellphones from home. The software development method uses the waterfall method starting from needs analysis, design, and implementation. testing the application using a black box shows the results are 100% running as expected. The results of the questionnaire test using the System Usability Scale method on a presence information system that is easy to use, user friendly and effective is stated by employees by 92%. It can be concluded that the application of an android-based information system during the COVID-19 pandemic is the most appropriate solution in solving problems in CV. Manha Digital